Context-oriented exception handling. (11th December 2009) - Dillenburg, Fabiane Cristine; Barbosa, Jorge Luis Victoria
The growing availability of small, faster computational devices has made mobile computing more popular in our daily life. The development of new applications demands an adoption of programming languages to this new reality, in order to take advantage of new available technologies. In this context, this paper presents a proposal for the specification of context-oriented exception handling features, aiming the development of mobile and ubiquitous applications. These features were implemented in the Holoparadigm mobile development and execution platform. Also, these features were tested using specially crafted applications that triggered exception handling.